The Influence Of Audit Committee, First Firm Reputation, Company Size, And Profitability On Audit Delay: - Safutri , Ria Wulanda; Masyitah, Emi; Liswanty , Ina (Universitas Dehasen Bengkulu, 2025)
The purpose of this study is to determine the influence of the Audit Committee, Public Accounting Firm Reputation, Company Size, and Profitability on Audit Delay. An empirical study of property and real estate sub-sector service companies listed on the Indonesia Stock Exchange in 2023-2024, both partially and simultaneously. This study uses a quantitative approach. The results of the study indicate that there is no influence between the Audit Committee on Audit Delay, no influence of Public Accounting Firm Reputation on Audit Delay, no influence of Company Size on Audit Delay, no influence of Profitability on Audit Delay. Based on the research conducted on property and real estate sub-sector service companies listed on the Indonesia Stock Exchange in 2023-2024, it can be concluded that there is a simultaneous influence of the Audit Committee, Public Accounting Firm Reputation, Company Size, and Profitability on Audit Delay. The R-Square value of 7.1% means that 7.1% of the variation in the Audit Delay value is determined by the role of the variation in the values of the Audit Committee, KAP Reputation, Company Size and Profitability, in other words the contribution of the Audit Committee, KAP Reputation, Company Size and Profitability in influencing Audit Delay is 7.1% while the remaining 92.9% is influenced by other variables not included in this study.